2020
DOI: 10.1177/0956462419878333
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of bacterial vaginosis in HIV-infected women in Maharashtra, India

Abstract: We evaluated the prevalence and determinants of bacterial vaginosis (BV) in HIV-infected women from Maharashtra, India. Among 912 HIV-infected women enrolled, BV was diagnosed in 191 (20.9%) and intermediate BV was diagnosed in 258 (28.3%) women. Women with more than two pregnancies had 1.6 times increased risk of BV (95% CI 1.0, 2.5, p-value 0.038), women who were menopausal had 6.2 times increased risk of BV (95% CI 2.4, 15.6, p-value <0.001) and women who were human papillomavirus (HPV) positive had 2.3 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…HIV positive women co-infected with HPV are 2.3 times more likely to have BV and BVAB1, BVAB 2 and BVAB 3 are indicators of BV in these women [21,22]. We report a Despite an observation of A. vaginae and G. vaginalis in over 80% of Mexican women, there was no association to HPV infection; authors concluded that these bacteria might be part of the normal microbiome [23].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…HIV positive women co-infected with HPV are 2.3 times more likely to have BV and BVAB1, BVAB 2 and BVAB 3 are indicators of BV in these women [21,22]. We report a Despite an observation of A. vaginae and G. vaginalis in over 80% of Mexican women, there was no association to HPV infection; authors concluded that these bacteria might be part of the normal microbiome [23].…”
Section: Discussionmentioning
confidence: 56%
“…HIV positive women co-infected with HPV are 2.3 times more likely to have BV and BVAB1, BVAB 2 and BVAB 3 are indicators of BV in these women [ 21 , 22 ]. We report a statistically significant association of BVAB 1 and 3 and an increased detection of BVAB 2 in women co-infected with HPV.…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, compared with the frequency of HIV-1 in women with normal vaginal flora (14.2%), a markedly elevated frequency (26.7%) was observed in women with severe BV (Nugent scores 9-10) (Ledru et al, 1997). Similarly, a study on HIV-infected Indian women showed the elevated risk of BV in HIV-infected and HPV-positive women and the high prevalence of BV among women infected with HIV (Joshi et al, 2020). Women with HIV -BV + , HIV -BV -, HIV + BV -, and HIV + BV + were compared in terms of microbiota of the lower genital tract, and results showed that HIV infection was linked to increased diversity (Spear et al, 2008).…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 96%
“…1). Table 1 shows that of 13 eligible studies, eight were cross-sectional studies, 22,[40][41][42][43][44][45][46] three were cohort studies, [47][48][49] one was a nested case-control study 50 and one was a randomised controlled trial. 51 Three studies were from the USA, [47][48][49] three were from Italy, 22,45,46 and one study from each of the UK, 41 Kenya, 40 South Africa, 50 Brazil, 51 Greece, 44 China 43 and India.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…51 Three studies were from the USA, [47][48][49] three were from Italy, 22,45,46 and one study from each of the UK, 41 Kenya, 40 South Africa, 50 Brazil, 51 Greece, 44 China 43 and India. 42 The populations included were ethnically diverse, including Afro-Caribbean, 41 Asian 46 , Caucasian, 22,41,51 Central West African 46 , East European 46 , Han Chinese, 43 Hellenic, 44 Hispanic or Latina, 47,49 Indian subcontinent, 41 Italian, 46 Non-Hispanic African American, 49 Non-Hispanic Black, 47 Non-Hispanic White, 47,49 North African, 46 South American 46 and West European. 46 Four studies recruited participants from gynaecological clinics or inpatient gynaecological wards, 41,44,45,51 two were from community screening programs (cervical screening, employment screening), 22,43 three were from HIV-positive populations, 40,42,50 one was a population cohort, 48 two were community-based cohorts 47,…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%